Indigenous knowledge and antibacterial activity of selected herbs used locally to treat common cold in Central Uganda - Walugembe, Joel; Iramiot, Jacobs S.; Katuura, Esther (Journal of Medicinal Plants Research, 2016)
The study documented the medicinal plants used in the treatment of influenza and common cough and established efficacy of some plants locally used against bacteria causing upper respiratory tract infections in Uganda. It involved an ethnobotanical survey and laboratory experimental investigation to determine the bioactivity against selected bacteria that cause upper respiratory tract infections. Data on medicinal indigenous knowledge was collected with the aid of questionnaires, direct observations, key informant interviews and field excursions and voucher specimen collection. The plants were identified by a botanist at Makerere University Herbarium (MHU), Department of Biological Sciences and voucher specimen were deposited in the herbarium. Methanol and diethyl ether extracts of the commonly used plants were screened for antibacterial activity against Streptococcus pneumonia and Klebsiella pneumonia using agar well diffusion and agar well dilution methods. Ethno botanical survey showed that 43 plants were commonly used and the most commonly used plant was Momordica feotida. Three out of four extracts assayed had activity against S. pneumonia and K. pneumonia, while one showed activity against K. pneumoniae. Hence, plants extracts showed broad spectrum antimicrobial activity. There is need for further development and standardization of products to treat respiratory diseases at household level in the study area.
Keywords: Indigenous knowledge.; Medicinal plants; Bioactivity; Minimum inhibitory concentration (MIC); Upper respiratory infections